Distance and indices computation in chains and nanotubes model as graph discrete dynamica systems. Issue 1 (1st February 2017) - Wu, Hualong; Zhao, Bo; Gan, Jianhou; Gao, Wei
Abstract : The early study reveals that the biochemical and pharmacological properties of chemical pound is closely related to its molecular structure, and calculating the indices defined on molecular graphs based on certain chemical characteristics can help the researchers better understand the principles and features of new compounds, nanomaterials and drugs. In this paper, in terms of molecular structure analysis and distance computation, we determine several distance-based indices of penta-chains and zig-zag open-ended nanotubes.